Pengembangan dan Validasi Tes Komik Soal Berbasis Certainty of Response Index (CRI) Untuk Mendeteksi Miskonsepsi Siswa Sekolah Dasar - Qatrunnada, Assita Azka; Kurniawati, Wahyu (Borobudur Educational Review, 2026)
Misconceptions in science learning in elementary schools are often not properly identified because conventional evaluation tools usually only assess whether answers are right or wrong without revealing the level of students' confidence in their answers. This makes it difficult for teachers to distinguish between correct conceptual understanding, strong misconceptions, and answers obtained through guessing. This study aims to develop and validate a comic-based test using the Certainty of Response Index (CRI) as a diagnostic instrument to detect students' misconceptions about the material on the forms of matter and their changes. The research method used the 4D development approach developed by Thiagarajan. Validation was conducted through expert judgment involving one subject matter expert and one evaluation expert to assess content appropriateness, instrument construction, language clarity, and illustration quality. The validation results showed that the instrument had good content validity, communicative illustrations, and appropriate application of the CRI scale to identify students' confidence levels. Thus, CRI-based comic tests have the potential to be an interesting, contextual, and more comprehensive misconception detection tool compared to conventional tests in science learning in elementary schools.